Retinoic acid attenuates ischemic injury-induced activation of glial cells and inflammatory factors in a rat stroke model. - Ju-Bin Kang; Hyun-Kyoung Son; Murad-Ali Shah; Phil-Ok Koh (PLoS ONE, 2024)
Stroke is a leading cause of death and long-term disability which can cause oxidative damage and inflammation of the neuronal cells. Retinoic acid is an active metabolite of vitamin A that has various beneficial effects including antioxidant and anti-inflammatory effects. In this study, we investigated whether retinoic acid modulates oxidative stress and inflammatory factors in a stroke animal model. A middle cerebral artery occlusion (MCAO) was performed on adult male rats to induce focal cerebral ischemia. Retinoic acid (5 mg/kg) or vehicle was injected into the peritoneal cavity for four days before MCAO surgery. The neurobehavioral tests were carried out 24 h after MCAO and cerebral cortex tissues were collected. The cortical damage was assessed by hematoxylin-eosin staining and reactive oxygen species assay. In addition, Western blot and immunohistochemical staining were performed to investigate the activation of glial cells and inflammatory cytokines in MCAO animals. Ionized calcium-binding adapter molecule-1 (Iba-1) and glial fibrillary acidic protein (GFAP) were used as markers of microglial and astrocyte activation, respectively. Tumor necrosis factor-α (TNF-α) and interleukin-1β (IL-1β) were used as representative pro-inflammatory cytokines. Results showed that MCAO damage caused neurobehavioral defects and histopathological changes in the ischemic region and increased oxidative stress. Retinoic acid treatment reduced these changes caused by MCAO damage. We detected increases in Iba-1 and GFAP in MCAO animals treated with vehicle. However, retinoic acid alleviated increases in Iba-1 and GFAP caused by MCAO damage. Moreover, MCAO increased levels of nuclear factor-κB and pro-inflammatory cytokines, including TNF-α and IL-1β. Retinoic acid alleviated the expression of these inflammatory proteins. These findings elucidate that retinoic acid regulates microglia and astrocyte activation and modulates pro-inflammatory cytokines. Therefore, this study suggests that retinoic acid exhibits strong antioxidant and anti-inflammatory properties by reducing oxidative stress, inhibiting neuroglia cell activation, and preventing the increase of pro-inflammatory cytokines in a cerebral ischemia.